In-situ testing for characterizing the landslide deposit in Jiuzhaigou cultural heritage site after the 2017 earthquake - Pei, Xiangjun; Jiang, Tao; Cui, Shenghua; Guo, Bin; Liang, Jing (Frontiers in Earth Science, 2023)
The 2017 Jiuzhaigou earthquake caused numerous landslide masses in the Jiuzhaigou cultural heritage site, leading to frequent surface mass movements and affecting the hydrological landscape. This was the first time a strong earthquake hit the heritage site in China, making it an important area for ecological geological environment protection and restoration research. To understand the influence of slope runoff erosion on the activation of landslide accumulations, this study examined remote sensing images from 2017 to 2020 to investigate the geological disaster, while field scour tests were conducted to study the rainfall seepage, mass erosion, and migration.The results indicated that the steep-sloped landslide deposits in the heritage site contain a high content of fine grains and good permeability.